Pengaruh Metode Latihan Drilling Terhadap Peningkatan Akurasi dalam Melakukan Pukulan Smash pada Olahraga Bulutangkis - Mahendra, Muhamad Rifqi (Jurnal Porkes, 2024)
The purpose of this study was to reveal the effect of the drilling training method on improving accuracy in smash shots in badminton sports and to examine how much the effect of the drilling training method on improving accuracy in smash shots of badminton players. This study uses an experimental method and uses a pre-experiment design with a one group pretest posttest design type. The population in this study was 31 people. The sample in this study was 19 people who met the criteria. Data collection in this study was with a badminton smash accuracy measurement test. The results showed a sig value (2-tailed) of 0.000 ≤ 0.05 which means H1 is accepted and Ho is rejected. So the conclusion is that there is an effect of the complex drilling training method on increasing accuracy in smash shots in badminton sports, the value of R is a symbol of the correlation coefficient value of 0.622. From the results of the table above, the coefficient of determination (R Square) is 0.386 which means that the effect on the independent variable on the dependent variable is R Square x 100 = 38.6%. So, the effect of the application of the influence of the complex drilling training method on the accuracy of smash shots in badminton sports is 38.6%.